Differential exposure to drinking water contaminants in North Carolina: Evidence from structural topic modeling and water quality data. (15th June 2023) - Sohns, Antonia
Abstract: To better understand water security of communities in North Carolina, this research uses structural topic modeling (STM) and geographic mapping to identify the main topics and pollutant categories being researched and the areas exposed to drinking water contaminants. The textual data derived from the journal article abstracts that examined water pollution in North Carolina is from 1964 to present. The STM analysis of textual data is paired with socio-demographic data from the 2015–2019 American Community Survey (ACS) 5-year estimates and water pollution data from North Carolina state agencies. The STM findings show that the most discussed topics relate to runoff management, wastewater from concentrated agricultural feeding operations, emerging contaminants, land development, and health impacts as a result of water contamination. The article discusses how the topics especially threaten groundwater resources used by community water systems and private wells. Those communities served by private wells are predominantly low-income and minority populations. As a result, threats to groundwater supplies exacerbate existing issues of environmental justice in North Carolina, especially in the Coastal Plains Region. The STM findings revealed that several key threats to safe drinking water are less covered by academic literature, such as poultry concentrated agricultural feeding operations and climate impacts, which may increase disparities in water access in North Carolina. Highlights: Poultry concentrated agricultural feeding operations impact safe drinking water. Climate impacts may increase disparities in water access in North Carolina. Threats to groundwater supplies exacerbate environmental justice in North Carolina.